Procedimentos para manutenção de um trocador de calor do tipo casco e tubo - Doi, Vinícius Geraldo (2015)
Maintaining until recently was considered as a factor in costs and expenses. In the past, the best known aspects of maintenance were characterized as repetitive and routine services, pure spare parts, little technique, improvisation and emergencies. However due to its high impact on the "down time", machine stop during production, for managerial and technical causes, has been seen with new eyes, and is considered factor of quality and productivity, short of competitiveness. The exchangers as is very important in plants for heat transfer has to be done proactively and predictively maintenance, so that there is no reduction in machine stops, it may affect the whole process, resulting in delayed delivery or poor quality of the final product thus reducing their competitiveness.